IZIN PEMERIKSAAN TERHADAP ANGGOTA DPR OLEH APARAT PENEGAK HUKUM DIKAITKAN DENGAN PRINSIP NEGARA HUKUM - Isharyanto, Isharyanto; Lestari, Dwi (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
This paper aimed to know the change of the construction of investigation permission of parliament (DPR) members to become need the approval of the President as well as its relevance to the legal principles of the rule of law. This research is the normative legal research which areprescriptive. The permission construction changes as a consequence upon issuance the Constitutional Court decision number 76/PUU-XII/2014. The results showed that the change in investigation permission construction of Parliament (DPR) membersby law enforcement be require approval by the President because Mahkamah Kehormatan Dewan (MKD) is the institution of ethics that have no direct relationship with the criminal justice system. In addition, the DPR as State officials must be balanced with adequate judicial protection and proportionate, as well as an effort to uphold the mechanism of checks and balances between the holder of legislative powers and the holder of the executive power. Then investigation permission of members of Parliament are not relevant when it is associated with both the principle of rule of law, namely the equality before the law principle and independent and impartial judiciary principle.